Design of low-cost and simple reconstruction method for Three Dimensional Electrical Impedance Tomography (3D-EIT) Imaging - Endarko Endarko; Ari Bangkit Sanjaya Umbu (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2020)
Electrical impedance tomography is a non-invasive imaging modality that uses the electrical conductivity distribution to reconstruct images based on potential measurements from the object's surface. The proposed study was to design and fabricate a low-cost and simple reconstruction method for 3D electrical impedance tomography imaging. In this study, we have been successfully developed 3 Dimensional Electrical Impedance Tomography (3D-EIT) system using 16 copper electrodes (Cu) to detect and reconstruct the presence of objects in the Phantom. 3D-EIT was developed using Phantom as a test object with PVC pipe material, with an inner diameter of 7.2 cm and a height of 5.4 cm. Electrodes were arranged in two rings, with each ring having eight electrodes arranged in a planar line. Furthermore, the Gauss-Newton algorithm and Laplace prior regularization were used to image reconstruction of objects inside the Phantom using voltage measurement produced from sequential pairs of neighboring electrodes. The voltage is obtained from the injection of a constant current of 1 mA at 20 kHz into the system's electrode pairs. The objects used in this research are PVC pipe, solid aluminum, PVC pipes filled with wax glue, and copper trusses. The results obtained show that the reconstruction results can provide information about the position, the electrical properties, and the shape of real objects. Finally, the system can detect the location, height, and electrical properties of objects for all variations of angle and height variations.